Pengaruh Financial Literacy dan Financial Self-Efficacy terhadap Risky Credit Behavior dalam Penggunaan Paylater (Survei pada Mahasiswa di Kota Tasikmalaya) - Ernawati Ernawati; Rita Tri Yusnita; Gian Riksa Wibawa (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This study aims to determine the effect of financial literacy and financial self-efficacy on risky credit behavior in using paylater (survey of students in tasikmalaya city). The method used in this research is a quantitative method through a survey approach. With a research sample of 100 students in Tasikmalaya City who use PayLater. The data used is using primary data. The analytical tool used in this research is multiple regression using SPSS 26.0. The results showed that financial literacy has a good assessment classification, financial self-efficacy has a good assessment and risky credit behavior has a good assessment classification for students in Tasikmalaya City who use PayLater. Simultaneously financial literacy and financial self-efficacy have a significant influence on risky credit behavior. Partially, financial literacy does not have a significant effect on risky credit behavior and financial self-efficacy has a significant effect on risky credit behavior in students in Tasikmalaya City who use PayLater.